Respon Pertumbuhan dan Hasil Terong (Solanum melongena L.) Akibat Perbedaan Waktu Pemberian Pupuk Mikoriza: Growth Response and Yield of Eggplant (Solanum melongena L.) Due to Differences in Mycorrhizal Fertilizer Application Time - Afdila, Moch. Faizin; Hidayanto, Fajar (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2023)
Eggplant is a horticultural crop that contains vitamins and nutrients such as vitamin A, vitamin C, potassium, phosphorus, iron, protein and carbohydrates. Optimizing eggplant productivity can be supported by the application of mycorrhizal fertilizers as a provider of phosphorus elements and maintaining soil moisture. The aim of this study was to distinguish the timing of mycorrhizal fertilizer application in supporting eggplant productivity. The treatment was divided into three, namely P1: fertilizing two weeks before planting at a dose of 5 kg/ha; P2: fertilizing one week before planting at a dose of 5 kg/ha; and P3: fertilization at planting time of 5 kg/ha. Completely randomized design with 3 replications was tested in this study. The results of the study were that mycorrhizal fertilizers on vegetative observations tended to be better on the treatment at planting time compared to the other two treatments, but on vegetative observations at plant height at the age of 21 DAT the treatment 1 week before planting turned out to be superior to the other two treatments. Generative observations tended to have better results in the treatment 1 week before planting than the treatment at planting time which tended to have lower yields where the fresh weight of the fruit only weighed 150,35 grams while the treatment 2 weeks before planting had a fresh weight of 161,35 grams . The length of the treated fruit 1 week before planting was 27,35 cm far above the treatment at planting with a length of only 24,26 cm.